Delving deeper into the agricultural transformation and youth employment nexus: The Nigerian case - Adesugba, Margaret Abiodun; Mavrotas, George (International Food Policy Research Institute, 2016)
Youth employment is not an entirely new topic for research and policy. Recent estimates from the International Labour Organisation (ILO) (2013a) suggest that high and rising unemployment rates among youth remain a key challenge to global development, especially in the developing world. This is particularly important in sub-Saharan Africa where about 85 percent of youth (defined by the ILO as all those between the ages of 15 and 24 years) are poor, 70 percent live in rural areas where agriculture is the main source for their income and subsistence, and 11 million youth are expected to enter the labor market every year for the next decade (World Bank 2014). These characteristics of youth in sub-Saharan Africa justify the centrality of the nexus between youth employment and agriculture in formulating development policy on the continent. At the same time, youth unemployment is currently one of the issues receiving attention at the top of the global development agenda.